MEDIASI YANG DILALUKAN DILUAR PENGADILAN (NON LITIGASI) DALAM MENYELESAIKAN PERSELISIHAN HUBUNGAN INDUSTRIAL DI KOTA PONTIANAK - JANKA INDRIA SARI NIM. A1011171105 (Fakultas Hukum Universitas Tanjungpura, 2023)
Abstrac Company disputes/conflicts are common, in accordance with Law Number 2 of 2004 concerning Industrial Relations Dispute Settlement. Disputes in the field of Industrial Relations, which have been known so far, are regarding the rights stipulated, both in work agreements, company regulations and statutory regulations. Therefore, the role of the mediator is needed in managing disputes between workers and employers.The title of this research is as follows